2023
DOI: 10.1021/jacs.2c12311
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Alkyl–Silyl Cross-Coupling via Homolysis of Unactivated C(sp3)–O Bonds with the Cooperation of Gold Nanoparticles and Amphoteric Zirconium Oxides

Abstract: Since C­(sp3)–O bonds are a ubiquitous chemical motif in both natural and artificial organic molecules, the universal transformation of C­(sp3)–O bonds will be a key technology for achieving carbon neutrality. We report herein that gold nanoparticles supported on amphoteric metal oxides, namely, ZrO2, efficiently generated alkyl radicals via homolysis of unactivated C­(sp3)–O bonds, which consequently promoted C­(sp3)–Si bond formation to give diverse organosilicon compounds. A wide array of esters and ethers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Previously, we demonstrated the depolymerizative silylation of polyester by the Au/ZrO 2 catalyst and disilane. 44 Au/TiO 2 and hydrosilane were also effective for the depolymerization of poly(1,4-bulylene)succinate (PBS), and 1,4-disilylbutane (6) and disilylsuccinate (7) were obtained as main products in 41% and 60% yields, respectively (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we demonstrated the depolymerizative silylation of polyester by the Au/ZrO 2 catalyst and disilane. 44 Au/TiO 2 and hydrosilane were also effective for the depolymerization of poly(1,4-bulylene)succinate (PBS), and 1,4-disilylbutane (6) and disilylsuccinate (7) were obtained as main products in 41% and 60% yields, respectively (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…43 Our group recently reported that Au/ZrO 2 catalysts efficiently promoted the silylation of inactive C(sp 3 )−O bonds in alkyl acetates and alkyl ethers with disilanes to furnish alkylsilanes. 44 The key to success for the specific C(sp 3 )−Si bond formation is the single-electron oxidation of disilane by Au nanoparticles to generate silyl radicals. Subsequent attack of the alkyl acetate by silyl radical promotes homolysis of a stable C(sp 3 )−O bond to generate alkyl radicals, which couples with another silyl radical to afford alkylsilanes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37][38][39][40][41][42][43][44] Recently, we found that homolytic cleavage of a stable C(sp 3 )À O bond took place in the presence of a supported Au NPs catalyst, which realized radical alkyl-silyl cross-coupling to give alkylsilanes (Scheme 1). [45,46] Singleelectron oxidation of disilane triggered the fragmentation of a SiÀ Si bond to furnish highly reactive silyl radicals, [47] implying that supported Au NPs function as heterogeneous single-electron transfer catalysts without light irradiation. Against this background, we envisaged that supported Au NPs catalysts could promote radical cross-coupling via single-electron transfer from disilanes to redox-active esters such as N-hydroxy phthalimide (NHPI) ester.…”
Section: Introductionmentioning
confidence: 99%
“…Size-specific oxidation catalysis by gold has stimulated researchers to elucidate its origin and to explore new catalytic properties. We have addressed these fundamental issues using monodisperse Au nanoparticles (NPs) weakly stabilized by poly­(vinylpyrrolidone) (Au:PVP) as a model system and found that the catalytic activity for alcohol oxidation was monotonically enhanced as the average diameter decreased to ∼1 nm. , Meanwhile, we recently achieved atomically precise synthesis of Au:PVP clusters such as Au 24 :PVP and Au 38 :PVP and revealed that the activity of Au 38 :PVP was higher than that of Au 24 :PVP . This result suggests that the catalytic activity is maximized at a certain size in the diameter range of 1–2 nm.…”
Section: Introductionmentioning
confidence: 99%